High-speed rail damping surface back plate based on anticorrosive coating and preparation method of high-speed rail damping surface back plate
By applying improved anticorrosion coating and modified polyurethane resin on the high-speed rail damping back plate, a protective layer with high adhesion and waterproof performance is formed, the problem of insufficient anticorrosion performance in the prior art is solved, and the corrosion resistance and waterproof performance of the back plate are significantly improved.
Patent Information
- Application Number
- CN202510113467.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-24
AI Technical Summary
The existing high-speed rail damping back plates have insufficient anti-corrosion performance in high-salt air environments, which are prone to aging and falling off problems, resulting in corrosion of metal substrates and affecting service life and safety.
A high-speed iron damping back plate based on anticorrosion coating is used to form a dense and uniform protective layer through an improved spraying process, and a modified polyurethane resin is added to improve waterproof, moisture-proof and moisture-resistant decomposition properties.
It significantly improves the corrosion, waterproof and water-resistant decomposition properties of the back plate, ensures excellent adhesion of the anti-corrosion coating under long-term corrosive media and moisture infestation, avoids bubbles, cracks and oxidation, and is suitable for high-salinity coastal environments.
Smart Images

Figure BDA0005257237310000131 
Figure BDA0005257237310000141
Abstract
Description
Technical Field
[0001] The present application relates to the field of damping surface back plates, and more specifically mentions a high-speed rail damping surface back plate based on an anti-corrosion coating and a preparation method thereof. Background Art
[0002] With the continuous expansion of the high-speed railway network, the damping back plate of the high-speed railway, as an important part of the external structure of the high-speed train, not only needs to withstand the noise and vibration generated by the vehicle operation, but also needs to have excellent anti-corrosion performance to cope with various harsh environmental conditions. Especially in coastal areas, due to the high salt content in the air, higher requirements are placed on the corrosion resistance of the damping back plate.
[0003] Existing high-speed rail damping panels are usually made of metal materials and coated with anti-corrosion coatings to protect them from environmental factors. However, traditional anti-corrosion coatings do not perform well in high-salinity air environments and are prone to aging, peeling, and other problems, which lead to corrosion of the metal substrate, thereby affecting the service life and safety of the entire sound barrier system. In addition, the existing technology does not give enough consideration to how to effectively reduce the accumulation of salt mist on the panels, and lacks targeted designs to optimize the waterproof and moisture-resistant functions, making it easier for salt to adhere to the surface for a long time or even penetrate and contact metal materials, thereby accelerating the corrosion process. Summary of the invention
[0004] Therefore, in order to effectively solve the above-mentioned existing problems, the present application provides a high-speed rail damping back panel based on an anti-corrosion coating and a preparation method thereof. It mainly consists of two parts: one is the back panel itself, and the other is a special anti-corrosion coating. The presence of the anti-corrosion coating not only maintains the excellent corrosion resistance and weather resistance of the back panel, but also can greatly improve its own waterproof, moisture-resistant, and moisture-resistant properties; the anti-corrosion coating forms a dense, uniform, and highly adhesive back panel surface protective layer through an improved spraying process, which can maintain the excellent adhesion of the anti-corrosion coating even under long-term corrosive media and moisture intrusion, and can also effectively avoid blistering, cracking, and oxidation. It is especially suitable for the air environment with high salt content in coastal areas, and has a very excellent application effect.
[0005] As a preferred embodiment, the high-speed railway damping surface back plate based on the anti-corrosion coating has a structure including a metal back plate layer as a substrate and an anti-corrosion coating located on the surface of the metal back plate layer.
[0006] As a preferred implementation, the thickness of the metal back plate layer is 2 to 4 mm.
[0007] As a preferred implementation, the material of the metal back plate layer is any one of aluminum alloy, stainless steel or magnesium alloy.
[0008] As a preferred implementation, the material of the metal back plate layer is aluminum alloy.
[0009] As a preferred embodiment, the thickness of the anti-corrosion coating is 60 to 120 μm.
[0010] As a preferred implementation, the thickness of the anti-corrosion coating is 80-100 μm.
[0011] As a preferred embodiment, the anti-corrosion coating comprises, by weight, 40 to 60 parts of epoxy resin, 10 to 20 parts of modified functional resin, 15 to 25 parts of zinc-aluminum composite particles, 10 to 20 parts of functional filler, 3 to 6 parts of silane coupling agent, 1 to 3 parts of UV resistant agent, 1.5 to 2.5 parts of anti-settling agent, 3 to 8 parts of auxiliary agent, 1 to 3 parts of curing agent, and 10 to 25 parts of solvent.
[0012] As a preferred embodiment, the epoxy resin is bisphenol A epoxy resin or bisphenol F epoxy resin.
[0013] As a preferred embodiment, the epoxy resin is bisphenol A epoxy resin.
[0014] As a preferred embodiment, the mass ratio of the epoxy resin, the modified functional resin and the zinc-aluminum composite particles is (48-54): (12-19): (16-22).
[0015] As a preferred embodiment, the mass ratio of the epoxy resin, the modified functional resin and the zinc-aluminum composite particles is (50-53): (14-18): (17-19).
[0016] As a preferred embodiment, the modified functional resin is a modified polyurethane resin.
[0017] As a preferred embodiment, the preparation method of the modified polyurethane resin specifically includes the following steps: S1: adding polypropylene glycol to a reaction container and stirring at room temperature for 10 to 15 minutes, slowly adding 4,4'-diphenylmethane diisocyanate, maintaining the temperature at 50 to 60°C and stirring for 20 to 30 minutes to ensure uniform mixing; S2: adding hexafluorobutanol, N,N'-bis(2-hydroxyethyl)adipamide and trimethylolpropane triacrylate under continuous stirring, stirring sufficiently after each addition to ensure uniform distribution, heating to 80 to 90°C, adding stannous octoate and keeping warm for reaction for 4 to 5 hours; S3: after the reaction in S2 is completed, heating to 105 to 115°C, adding N-hydroxymethyl acrylamide and dibenzoyl peroxide, keeping warm for reaction for 3 to 4 hours, naturally cooling to room temperature after completion, sealing and storing at room temperature overnight, and obtaining the product after completion.
[0018] As a preferred embodiment, the number average molecular weight of the polypropylene glycol is 2000-2400 Da.
[0019] As a preferred embodiment, the mass ratio of the polypropylene glycol to 4,4'-diphenylmethane diisocyanate is (46-48): (38-42).
[0020] As a preferred embodiment, the mass ratio of 4,4'-diphenylmethane diisocyanate, hexafluorobutanol, N,N'-bis(2-hydroxyethyl)adipamide and trimethylolpropane triacrylate is (38-42):(3.5-4.5):(5-6):(3.5-4).
[0021] As a preferred embodiment, the mass ratio of trimethylolpropane triacrylate to N-methylol acrylamide is (3.5-4):(1.2-1.5).
[0022] By adding modified polyurethane resin as a modified functional resin, the anti-corrosion, waterproof and water decomposition resistance of the backplane can be greatly improved. The multi-active functional groups contained in the polyurethane resin can greatly increase the cross-linking density within the resin system and greatly enhance the interaction and adhesion between the resin molecular chains, thereby forming a denser three-dimensional molecular chain network, thereby greatly enhancing the resistance of the anti-corrosion coating to molecular chain slippage after curing, avoiding the appearance of silver-like cracks on the coating surface, reducing the size of the micropores on the coating surface, reducing the presence of internal particles and the continuity of the micropores, and on the other hand, improving the penetration barrier for water molecules and the overall spatial steric hindrance of the coating after curing, inhibiting the free rotation and movement frequency of the internal resin chain segments, and reducing unnecessary internal interactions during the curing period, thereby greatly enhancing the water resistance and decomposition resistance of the coating.
[0023] As a preferred embodiment, the mass ratio of zinc to aluminum in the zinc-aluminum composite particles is (0.8-1): (0.8-1).
[0024] As a preferred embodiment, the mass ratio of zinc to aluminum in the zinc-aluminum composite particles is 1:1.
[0025] As a preferred embodiment, the average particle size of the zinc-aluminum composite particles is 10 to 15 μm.
[0026] As a preferred embodiment, the functional filler is a composition of pigment particles and wear-resistant particles.
[0027] As a preferred embodiment, the mass ratio of the pigment particles to the wear-resistant particles is (6-10):(2-5).
[0028] As a preferred embodiment, the mass ratio of the pigment particles to the wear-resistant particles is (7-8): (3-3.5).
[0029] As a preferred embodiment, the pigment particles are at least one of zinc oxide, titanium dioxide, iron oxide red and carbon black.
[0030] As a preferred embodiment, the pigment particles are zinc oxide or titanium dioxide.
[0031] As a preferred embodiment, the wear-resistant particles are silicon dioxide.
[0032] As a preferred embodiment, the average particle size of the silicon dioxide is 10 to 20 nm.
[0033] As a preferred embodiment, the silane coupling agent is a composition of 3-aminopropyltriethoxysilane and 3-glycidyloxypropyltrimethoxysilane.
[0034] As a preferred embodiment, the mass ratio of 3-aminopropyltriethoxysilane to 3-glycidyloxypropyltrimethoxysilane is (2-2.5):(4-5).
[0035] As a preferred embodiment, the UV-resistant agent is 2-(2'-hydroxy-5'-methylphenyl)benzotriazole or 2,4-dihydroxybenzophenone.
[0036] As a preferred embodiment, the UV-resistant agent is 2-(2'-hydroxy-5'-methylphenyl)benzotriazole.
[0037] As a preferred embodiment, the anti-settling agent is a composition of hydrogenated castor oil and polyethylene wax.
[0038] As a preferred embodiment, the mass ratio of the hydrogenated castor oil to the polyethylene wax is (3-4): (1-1.8).
[0039] As a preferred embodiment, the mass ratio of the hydrogenated castor oil to the polyethylene wax is (3-3.5): (1.3-1.5).
[0040] As a preferred embodiment, the auxiliary agent is a composition of hexafluoroisopropyl vinyl ether and polyether-modified polysiloxane.
[0041] As a preferred embodiment, the mass ratio of hexafluoroisopropyl vinyl ether to polyether-modified polysiloxane is (4-4.2):(2.2-2.5).
[0042] As a preferred embodiment, the viscosity of the polyether-modified polysiloxane is 500-1500 cP, condition: 25°C.
[0043] As a preferred embodiment, the viscosity of the polyether-modified polysiloxane is 800-1000 cP, condition: 25°C.
[0044] As a preferred embodiment, the curing agent is polyoxypropylene diamine.
[0045] As a preferred embodiment, the solvent is propylene glycol methyl ether acetate.
[0046] As a preferred embodiment, the preparation method of the high-speed railway damping surface back plate based on the anti-corrosion coating specifically includes the following steps: S1: stirring the epoxy resin and the modified functional resin in a mixing container at room temperature, the stirring speed is 600-800rpm, the stirring time is 30-40min, after the stirring is completed, the zinc-aluminum composite particles, functional fillers and anti-settling agents are added, and then the stirring is continued at the same speed for 20-30min until all the solid particles are evenly dispersed; S2: adding silane coupling agent, UV resistant agent and auxiliary agent, stirring at a high speed of 1200-1500rpm in a high-speed disperser for 40-50min, then adding curing agent and solvent and adjusting to the required viscosity, sieving 200-250 mesh to remove large particles, and obtaining the anti-corrosion coating material; S3: spraying the anti-corrosion coating material on the surface of the metal back plate layer including the drainage groove, heating to 80-100℃, keeping warm and curing for 2-3h, and obtaining it after the curing is completed.
[0047] It should be specially noted that the high-speed rail damping surface back plate based on anti-corrosion coating prepared in the present application is a back plate structure belonging to the outside of the damping structure, and its function is to provide external back plate protection for the damping structure. The back plate itself does not have damping properties.
[0048] The beneficial effects of this application are:
[0049] 1. A high-speed rail damping surface back panel based on an anti-corrosion coating provided in the present application not only maintains the excellent anti-corrosion and weather resistance of the back panel, but also can greatly improve its own waterproof, moisture-resistant, and moisture-resistant properties; the specific anti-corrosion coating on the surface forms a dense, uniform, and highly adhesive back panel surface protective layer, which can maintain the excellent adhesion of the anti-corrosion coating even under long-term intrusion of corrosive media and moisture, and can also effectively avoid blistering, cracking, and oxidation. It is especially suitable for the air environment with a high salt content in coastal areas, and has a very excellent application effect.
[0050] 2. A high-speed rail damping surface back panel based on an anti-corrosion coating provided in the present application can greatly improve the anti-corrosion, waterproof and water decomposition resistance of the back panel by adding modified polyurethane resin as a modified functional resin; the modified polyurethane resin greatly enhances the interaction and adhesion between the resin molecular chains, thereby forming a denser three-dimensional molecular chain network, thereby greatly enhancing the resistance of the anti-corrosion coating to molecular chain slippage after curing, and avoiding the appearance of silver-like cracks on the coating surface, and reducing the size of the micropores on the coating surface, reducing the presence of internal particles and the continuity of the micropores, providing a solid foundation for the waterproof, corrosion-resistant and decomposition-resistant properties of the back panel.
[0051] 3. The high-speed rail damping surface back panel based on the anti-corrosion coating provided in the present application, the modified functional resin added therein can also work together with the specific additives added in the present application to further enhance the waterproof effect of the back panel surface, reduce cracks, breakage and the like, and through the surface aggregation effect, form a smoother and more regular coating surface, thereby greatly reducing the number of surface hydrated phases, thereby reducing the probability of penetration of water and active molecules, and helping to enhance corrosion resistance, waterproofness and other properties. DETAILED DESCRIPTION
[0052] The specific implementation examples will be used to more intuitively demonstrate and illustrate the contents of the invention content of this application. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification and should not limit the scope of the claims to be protected by this application.
[0053] Example 1
[0054] The high-speed rail damping surface back plate based on anti-corrosion coating has a structure comprising a metal back plate layer as a substrate and an anti-corrosion coating located on the surface of the metal back plate layer.
[0055] The thickness of the metal backing layer is 3.2 mm; the thickness of the anti-corrosion coating is 85 μm.
[0056] The material of the metal back plate layer is high-strength aluminum alloy 6061-T6.
[0057] The raw materials of the anti-corrosion coating, calculated by mass, are: 50.6 parts of epoxy resin, 16.8 parts of modified functional resin, 18.5 parts of zinc-aluminum composite particles, 14.5 parts of functional filler, 3.8 parts of silane coupling agent, 1.8 parts of UV resistant agent, 2.1 parts of anti-settling agent, 6.5 parts of auxiliary agent, 1.4 parts of curing agent and 12.5 parts of solvent.
[0058] The epoxy resin is bisphenol A epoxy resin, purchased from China Baling Petrochemical Co., Ltd., model E44.
[0059] The modified functional resin is a modified polyurethane resin; the preparation method of the modified polyurethane resin specifically includes the following steps, calculated by mass: S1: adding 47.6 parts of polypropylene glycol to a reaction container and stirring at room temperature for 15 minutes, slowly adding 41.2 parts of 4,4'-diphenylmethane diisocyanate, maintaining the temperature at 55°C and stirring for 25 minutes to ensure uniform mixing; S2: adding 4.2 parts of hexafluorobutanol, 5.5 parts of N,N'-bis(2-hydroxyethyl)adipamide and 3.8 parts of trimethylolpropane triacrylate under continuous stirring, stirring fully after each addition to ensure uniform distribution, heating to 85°C, adding 0.23 parts of stannous octoate and keeping warm for reaction for 4.5 hours; S3: after the reaction of S2 is completed, heating to 110°C, adding 1.6 parts of N-hydroxymethyl acrylamide and 0.03 parts of dibenzoyl peroxide, keeping warm for reaction for 3.5 hours, naturally cooling to room temperature after completion, sealing and storing at room temperature overnight, and obtaining the product after completion.
[0060] The number average molecular weight of polypropylene glycol was 2200 Da, and it was purchased from Haian Petrochemical Co., Ltd. in Jiangsu Province, China.
[0061] The mass ratio of zinc to aluminum in the zinc-aluminum composite particles is 1:1.
[0062] The average particle size of the zinc-aluminum composite particles was 12.8 μm.
[0063] The functional filler is a composition of pigment particles and wear-resistant particles, and the mass ratio of the two is 7.5:3.2.
[0064] The pigment particles are titanium dioxide.
[0065] The wear-resistant particles are silicon dioxide with an average particle size of 15 nm.
[0066] The silane coupling agent is a composition of 3-aminopropyltriethoxysilane and 3-glycidyloxypropyltrimethoxysilane, and the mass ratio of the two is 2.3:4.5.
[0067] The UV-resistant agent is 2-(2'-hydroxy-5'-methylphenyl)benzotriazole.
[0068] The anti-settling agent is a composition of hydrogenated castor oil and polyethylene wax, and the mass ratio of the two is 3.5:1.3.
[0069] The auxiliary agent is a composition of hexafluoroisopropyl vinyl ether and polyether modified polysiloxane, and the mass ratio of the two is 4:2.5.
[0070] The viscosity of the polyether-modified polysiloxane is 850 cP, condition: 25° C., and the corresponding viscosity product was purchased from Hubei Xinyuhong Biopharmaceutical Technology Co., Ltd., China.
[0071] The curing agent is polyoxypropylene diamine, which is purchased from Jeffamine D-230 sold by Huntsman Corporation in the United States.
[0072] The solvent is propylene glycol methyl ether acetate.
[0073] The preparation method of the high-speed rail damping surface backboard based on the anti-corrosion coating specifically includes the following steps: S1: Stirring the epoxy resin and the modified functional resin in a mixing container at room temperature at a stirring speed of 650rpm for 35min, adding zinc-aluminum composite particles, functional fillers and anti-settling agents after the stirring is completed, and then continuing to stir at the same speed for 25min until all the solid particles are evenly dispersed; S2: Adding silane coupling agent, UV resistant agent and auxiliary agent, stirring at a high speed of 1400rpm in a high-speed disperser for 45min, then adding curing agent and solvent and adjusting to the required viscosity, sieving through 240 mesh to remove large particles, and obtaining the anti-corrosion coating material; S3: Spraying the anti-corrosion coating material on the surface of the metal backboard layer including the drainage groove, heating to 90°C, and heat curing for 2.5h, and obtaining the coating material after the curing is completed.
[0074] Example 2
[0075] The only difference between this embodiment and Embodiment 1 is as follows: the raw materials of the anti-corrosion coating, in parts by mass, are: 48.2 parts of epoxy resin, 12 parts of modified functional resin, 21.6 parts of zinc-aluminum composite particles, 12.5 parts of functional filler, 3.2 parts of silane coupling agent, 1.6 parts of UV resistant agent, 1.8 parts of anti-settling agent, 6.8 parts of auxiliary agent, 1.2 parts of curing agent, and 9.8 parts of solvent.
[0076] The mass ratio of zinc to aluminum in the zinc-aluminum composite particles is 0.8:1.
[0077] The functional filler is a composition of pigment particles and wear-resistant particles, and the mass ratio of the two is 8:3.
[0078] The silane coupling agent is a composition of 3-aminopropyltriethoxysilane and 3-glycidyloxypropyltrimethoxysilane, and the mass ratio of the two is 2:5.
[0079] The auxiliary agent is a composition of hexafluoroisopropyl vinyl ether and polyether modified polysiloxane, and the mass ratio of the two is 4.2:2.2.
[0080] Example 3
[0081] The only differences between this embodiment and embodiment 1 are as follows: 54 parts of epoxy resin, 19 parts of modified functional resin, 16.5 parts of zinc-aluminum composite particles, 15.5 parts of functional filler, 4.1 parts of silane coupling agent, 2.1 parts of UV resistant agent, 2.2 parts of anti-settling agent, 6.2 parts of auxiliary agent, 1.6 parts of curing agent, and 18.8 parts of solvent.
[0082] The mass ratio of zinc to aluminum in the zinc-aluminum composite particles is 1:0.8.
[0083] The functional filler is a composition of pigment particles and wear-resistant particles, and the mass ratio of the two is 7:3.4.
[0084] The silane coupling agent is a composition of 3-aminopropyltriethoxysilane and 3-glycidyloxypropyltrimethoxysilane, and the mass ratio of the two is 2.5:4.
[0085] The auxiliary agent is a composition of hexafluoroisopropyl vinyl ether and polyether-modified polysiloxane, and the mass ratio of the two is 4.1:2.3.
[0086] Comparative Example 1
[0087] The only difference between this comparative example and Example 1 is as follows: the raw materials of the anti-corrosion coating, in parts by mass, are: 50.6 parts of epoxy resin, 6.5 parts of modified functional resin, 18.5 parts of zinc-aluminum composite particles, 14.5 parts of functional filler, 3.8 parts of silane coupling agent, 1.8 parts of UV resistant agent, 2.1 parts of anti-settling agent, 6.5 parts of auxiliary agent, 1.4 parts of curing agent, and 12.5 parts of solvent.
[0088] Comparative Example 2
[0089] The only difference between this comparative example and Example 1 is as follows: the raw materials of the anti-corrosion coating, in parts by mass, are: 50.6 parts of epoxy resin, 16.8 parts of modified functional resin, 18.5 parts of zinc-aluminum composite particles, 10.5 parts of functional filler, 3.8 parts of silane coupling agent, 1.8 parts of UV resistant agent, 2.1 parts of anti-settling agent, 2.4 parts of auxiliary agent, 1.4 parts of curing agent, and 12.5 parts of solvent.
[0090] Comparative Example 3
[0091] The only difference between this comparative example and Example 1 is as follows: the preparation method of the modified polyurethane resin specifically comprises the following steps, calculated by mass: S1: adding 60 parts of polypropylene glycol to a reaction container and stirring at room temperature for 15 minutes, slowly adding 35.5 parts of 4,4'-diphenylmethane diisocyanate, maintaining the temperature at 55°C and stirring for 25 minutes to ensure uniform mixing; S2: adding 4.2 parts of hexafluorobutanol, 5.5 parts of N,N'-bis(2-hydroxyethyl)adipamide and 3.8 parts of trimethylolpropane triacrylate under continuous stirring, stirring sufficiently after each addition to ensure uniform distribution, heating to 85°C, adding 0.23 parts of stannous octoate and keeping warm for reaction for 4.5 hours; S3: after the reaction of S2 is completed, heating to 110°C, adding 1.6 parts of N-hydroxymethyl acrylamide and 0.03 parts of dibenzoyl peroxide, keeping warm for reaction for 3.5 hours, naturally cooling to room temperature after completion, sealing and storing at room temperature overnight, and obtaining the product after completion.
[0092] Comparative Example 4
[0093] The only difference between this comparative example and Example 1 is as follows: the preparation method of the modified polyurethane resin specifically comprises the following steps, calculated by mass: S1: adding 47.6 parts of polypropylene glycol to a reaction container and stirring at room temperature for 15 minutes, slowly adding 41.2 parts of 4,4'-diphenylmethane diisocyanate, maintaining the temperature at 55°C and stirring for 25 minutes to ensure uniform mixing; S2: adding 2.1 parts of hexafluorobutanol, 1.2 parts of N,N'-bis(2-hydroxyethyl)adipamide and 1 part of trimethylolpropane triacrylate under continuous stirring, stirring sufficiently after each addition to ensure uniform distribution, heating to 85°C, adding 0.18 parts of stannous octoate and keeping warm for reaction for 4.5 hours; S3: after the reaction of S2 is completed, heating to 110°C, adding 0.2 parts of N-hydroxymethyl acrylamide and 0.01 parts of dibenzoyl peroxide, keeping warm for reaction for 3.5 hours, naturally cooling to room temperature after completion, sealing and storing at room temperature overnight, and obtaining the product after completion.
[0094] Comparative Example 5
[0095] The only difference between this comparative example and Example 1 is that the silane coupling agent is a composition of 3-aminopropyltriethoxysilane and 3-glycidyloxypropyltrimethoxysilane, and the mass ratio of the two is 3:1.
[0096] Comparative Example 6
[0097] The only difference between this comparative example and Example 1 is that the auxiliary agent is a composition of hexafluoroisopropyl vinyl ether and polyether-modified polysiloxane, and the mass ratio of the two is 8:1.
[0098] Comparative Example 7
[0099] The only difference between this comparative example and Example 1 is that the auxiliary agent is a composition of hexafluoroisopropyl vinyl ether and polyether-modified polysiloxane, and the mass ratio of the two is 1:1.
[0100] Performance Evaluation
[0101] 1. The surface salt spray corrosion resistance test of the backsheets prepared in the embodiment and the comparative example was carried out. The test environment temperature was 35±2°C, the humidity was 90±3%, the test solution was 7.5wt% NaCl solution, and the spraying rate was 2mL / 16h·80cm 2 , and obtain its salt spray corrosion resistance in hours, and the results are recorded in Table 1.
[0102] 2. The surface of the backsheet prepared in the embodiment and the comparative example was tested for water contact angle by the sessile drop method. The water drop volume was 3.5 μL and the recording time was 60 s. The final water contact angle was recorded and the results were recorded in Table 1.
[0103] 3. The backplanes prepared in the embodiments and comparative examples were tested for heat stability. The backplane samples were placed in a constant temperature and humidity chamber at a temperature of 60±2°C and a humidity of 75±2%, and observed for 6 months. After 6 months, the samples were taken out and observed to see if there were any damage, cracking, shedding or blistering. If so, they were marked as qualified, otherwise they were unqualified. 50 samples were tested in each group. If the number of unqualified samples was ≤2, it was marked as Class A. If 2<the number of unqualified samples was ≤5, it was marked as Class B. If the number of unqualified samples was>5, it was marked as Class C. The test level results are recorded in Table 1.
[0104] 4. The back panels prepared in the examples and comparative examples were subjected to a water boiling resistance decomposition test. The distance between the coating and the water surface was 0.5 m, the test water temperature was 96±2°C, and samples were taken every 2 hours for observation to see if the back panel anti-corrosion coating was damaged, cracked, detached, or bubbled. The test time (h) when the above phenomena first occurred was finally recorded, and the results are recorded in Table 1.
[0105] Table 1 Performance test results
[0106]
[0107]
[0108] From the final performance test results of the embodiments and comparative examples, comparative examples 1 to 7 achieved worse performance results than the embodiments, while the embodiments, because of the use of specific modified polyurethane resins and auxiliary agent combinations, can greatly enhance the resistance of the backplane anti-corrosion coating system to molecular chain slippage, avoid the appearance of silver-like cracks on the coating surface, reduce the size of the micropores on the coating surface, reduce the presence of internal particles and the continuity of the micropores, and on the other hand, improve the coating's penetration barrier to water molecules after curing and the overall steric hindrance, inhibit the free rotation and movement frequency of the internal resin chain segments, reduce unnecessary internal interactions during the curing period, and thus greatly enhance the coating's water resistance, corrosion resistance and decomposition resistance.
Claims
1. A high-speed rail damping back plate based on an anti-corrosion coating, characterized in that: The structure includes a metal backing plate layer as a substrate, and an anti-corrosion coating located on the surface of the metal backing plate layer; The thickness of the metal back plate layer is 2 to 4 mm; The material of the metal back plate layer is any one of aluminum alloy, stainless steel or magnesium alloy; The thickness of the anti-corrosion coating is 60 to 120 μm; The anti-corrosion coating comprises, by weight, 40 to 60 parts of epoxy resin, 10 to 20 parts of modified functional resin, 15 to 25 parts of zinc-aluminum composite particles, 10 to 20 parts of functional filler, 3 to 6 parts of silane coupling agent, 1 to 3 parts of UV-resistant agent, 1.5 to 2.5 parts of anti-settling agent, 3 to 8 parts of auxiliary agent, 1 to 3 parts of curing agent, and 10 to 25 parts of solvent. The epoxy resin is bisphenol A epoxy resin or bisphenol F epoxy resin; The modified functional resin is a modified polyurethane resin; The mass ratio of zinc to aluminum in the zinc-aluminum composite particles is (0.8-1): (0.8-1); The functional filler is a composition of pigment particles and wear-resistant particles; the mass ratio of the pigment particles to the wear-resistant particles is (6-10):(2-5).
2. The high-speed rail damping surface back plate based on the anti-corrosion coating according to claim 1 is characterized in that: The mass ratio of the epoxy resin, the modified functional resin and the zinc-aluminum composite particles is (48-54): (12-19): (16-22).
3. The high-speed rail damping surface back plate based on the anti-corrosion coating according to claim 2 is characterized in that: The preparation method of the modified polyurethane resin specifically comprises the following steps: S1: adding polypropylene glycol to a reaction container and stirring at room temperature for 10 to 15 minutes, slowly adding 4,4'-diphenylmethane diisocyanate, maintaining the temperature at 50 to 60°C and stirring for 20 to 30 minutes to ensure uniform mixing; S2: adding hexafluorobutanol, N,N'-bis(2-hydroxyethyl)adipamide and trimethylolpropane triacrylate under continuous stirring, fully stirring after each addition to ensure uniform distribution, heating to 80 to 90°C, adding stannous octoate and keeping the temperature for reaction for 4 to 5 hours; S3: after the reaction in S2 is completed, heating to 105 to 115°C, adding N-hydroxymethyl acrylamide and dibenzoyl peroxide, keeping the temperature for reaction for 3 to 4 hours, and naturally cooling to room temperature after completion, sealing and storing at room temperature overnight, and obtaining the product after completion; The mass ratio of the polypropylene glycol to 4,4'-diphenylmethane diisocyanate is (46-48): (38-42); The mass ratio of the 4,4'-diphenylmethane diisocyanate, hexafluorobutanol, N,N'-bis(2-hydroxyethyl)adipamide and trimethylolpropane triacrylate is (38-42):(3.5-4.5):(5-6):(3.5-4).
4. The high-speed rail damping surface back plate based on the anti-corrosion coating according to claim 3 is characterized in that: The number average molecular weight of the polypropylene glycol is 2000-2400 Da.
5. The high-speed rail damping surface back plate based on the anti-corrosion coating according to claim 4 is characterized in that: The mass ratio of the trimethylolpropane triacrylate to N-methylol acrylamide is (3.5-4):(1.2-1.5).
6. The high-speed rail damping surface back plate based on the anti-corrosion coating according to claim 5 is characterized in that: The average particle size of the zinc-aluminum composite particles is 10 to 15 μm.
7. The high-speed rail damping surface back plate based on the anti-corrosion coating according to claim 6 is characterized in that: The wear-resistant particles are silicon dioxide; the average particle size of the silicon dioxide is 10 to 20 nm.
8. The high-speed rail damping surface back plate based on the anti-corrosion coating according to claim 7 is characterized in that: The silane coupling agent is a composition of 3-aminopropyltriethoxysilane and 3-glycidyloxypropyltrimethoxysilane; the mass ratio of 3-aminopropyltriethoxysilane to 3-glycidyloxypropyltrimethoxysilane is (2-2.5): (4-5).
9. The high-speed rail damping surface back plate based on the anti-corrosion coating according to claim 8 is characterized in that: The auxiliary agent is a composition of hexafluoroisopropyl vinyl ether and polyether-modified polysiloxane; the mass ratio of the hexafluoroisopropyl vinyl ether and the polyether-modified polysiloxane is (4-4.2):(2.2-2.5); the viscosity of the polyether-modified polysiloxane is 500-1500 cP, and the condition is 25°C.
10. A method for preparing a high-speed railway damping surface back plate based on an anti-corrosion coating according to any one of claims 1 to 9, characterized in that: The specific steps include: S1: Stir the epoxy resin and modified functional resin in a mixing container at room temperature at a speed of 600-800 rpm for 30-40 min. After the stirring is completed, add zinc-aluminum composite particles, functional fillers and anti-settling agents, and then continue to stir at the same speed for 20-30 min until all the solid particles are evenly dispersed; S2: Add silane coupling agent, UV resistant agent and auxiliary agent, stir at a high speed of 1200-1500 rpm in a high-speed disperser for 40-50 min, then add curing agent and solvent and adjust to the required viscosity, sieve 200-250 mesh to remove large particles, and obtain an anti-corrosion coating material; S3: Spray the anti-corrosion coating material on the surface of the metal back plate layer including the drainage groove, heat to 80-100°C, and keep warm for 2-3 hours to obtain the coating after the curing is completed.
Citation Information
Patent Citations
Zinc-aluminum paint applied to steel transformer radiator surface and preparation method thereof
CN104356867A
Visible light cured heavy anticorrosion coating and preparation method thereof
CN110256953A
Heavy-duty anti-corrosion coating matching system for steel structure and preparation method of heavy-duty anti-corrosion coating matching system
CN117467337A
Wear-resistant anticorrosive paint and preparation method thereof
CN118480299A
Anti-corrosion powder coating for fire-fighting pipeline and preparation method of anti-corrosion powder coating
CN118599399A